Fundamentals of differential equations - Nagle, R. Kent (Addison-Wesley, 2000)
The texts also allow optional use of Computer Algebra Systems, with many exercises and projects included to let students use software to solve interesting and realistic problems and exercises. Necessary proofs in a conceptual presentation are always included, but may be skipped, allowing flexibility in the level of coverage of proofs. Technical Writing Exercises are included at the end of most chapters, to build students communication skills. Methods for approximating solutions to numerical algorithms are presented, along with computer program outlines, and are introduced early in the text.